Baited pots as an alternative fishing gear in the Norwegian fishery for Atlantic cod (Gadus morhua) - Olsen, Leonore (UiT The Arctic University of Norway, 2014)
The main objective of this thesis has been to record the degree of efficiency in two different types of pot designs, both constructed for catching cod (Gadus morhua). The two types of technologies were a Canadian cod pot developed by Centre for Sustainable Aquatic Resources (CSAR) at the Fisheries and Marine Institute of Memorial University of Newfoundland Canada and a Norwegian two-chamber pot developed by the Norwegian Institute for Marine Research. For having the possibility of comparing catch rates and as an indicator of the amount of target species and possible by-catch available in trial areas, bottom gillnets were used. Our results show low catch rates in both types of pots, with a high degree of variation. The highest catch rates produced by the pots are caught inshore with low sea current conditions. Both pot types have interesting by-catch profiles and the quality of catch is superior. Analyses of cod behaviour in relation to the pot structures indicated possibilities for further utilisation of vision stimuli in pot fishing, which could possibly result in higher catch rates